Intraperitoneal Solitary Fibrous Tumor. (7th September 2014) - Benabdejlil, Youssef; Kouach, Jaouad; Babahabib, Abdellah; Elhassani, Moulay Elmehdi; Rharassi, Issam; Boudhas, Adil; Bakkali, Hicham; Elmarjany, Mohammed; Moussaoui, Driss; Dehayni, Mohamed
Abstract : Solitary fibrous tumors of the pelvis are rare. We report the case of a 32-years-old patient who presented with abdominopelvic mass. The imaging studies showed a right adnexal mass of more than 10 cm. Exploratory laparotomy revealed a 20 cm mass at the Douglas pouch which was adhered to the posterior wall of the uterus. Complete resection of the mass was performed. Histological analysis showed a spindle cell undifferentiated tumor whose morphological and immunohistochemical profile are consistent with solitary fibrous tumor. It is important to know that although these tumors are rare, their evolution can be pejorative. Therefore, long-term followup should be recommended.